A common standard for the evaluation of public engagement with research. (25th January 2018) - Reed, Mark; Duncan, Sophie; Manners, Paul; Pound, Diana; Armitage, Lucy; Frewer, Lynn; Thorley, Charlotte; Frost, Bryony
Despite growing interest in public engagement with research, there are many challenges to evaluating engagement. Evaluation findings are rarely shared or lead to demonstrable improvements in engagement practice. This has led to calls for a common 'evaluation standard' to provide tools and guidance for evaluating public engagement and driving good practice. This paper proposes just such a standard. A conceptual framework summarizes the three main ways in which evaluation can provide judgements about, and enhance the effectiveness of, public engagement with research. A methodological framework is then proposed to operationalize the conceptual framework. The standard is developed via a literature review, semi-structured interviews at Queen Mary University of London and an online survey. It is tested and refined in situ in a large public engagement event and applied post hoc to a range of public engagement impact case studies from the Research Excellence Framework. The goal is to standardize good practice in the evaluation of public engagement, rather than to use standard evaluation methods and indicators, given concerns from interviewees and the literature about the validity of using standard methods or indicators to cover such a wide range of engagement methods, designs, purposes and contexts. Adoption of the proposed standard by funders of public engagement activities could promote more widespread, high-quality evaluation, and facilitate longitudinal studies to draw our lessons for the funding and practice of public engagement across the higher education sector.